Martial arts pedagogies and practice: A report on the contributions to coaching knowledge - Jennings, George (Revista de Artes Marciales Asiáticas, 2017)
The 4th International Coaching Conference held at Cardiff Metropolitan University, UK, showcased a range of studies concerning pedagogy in martial arts (MA). They varied in regards to their underpinning discipline, theory and method, but were united by a concern for enhancing practice in both pedagogy (the science) and pedagogies (the objects of study). One theoretical talk advocated a study of individual practices (techniques of the body and their corresponding methods) via praxiography in relation for a balanced, critical health pedagogy examining the duality of ‘dark’ and ‘light’ aspects. This in turn was applied by an emerging study looking at rapid weight loss practices in Judo and other combat sports that is beginning to scrutinise policies in order to regular this problem. Meanwhile, an investigation into the mental toughness of Karate practitioners uncovered similarly alarming findings on extreme training methods among veteran Welsh Karateka, while another study of a British context of Savate and Capoeira shared ways of studying MA pedagogies in their total form through traditional approach to ethnography. Together, these papers exemplify the increasing corpus of knowledge on teaching and learning in MA that could support that of coaching alongside sport and body pedagogy.